2002
DOI: 10.1002/pen.10976
|View full text |Cite
|
Sign up to set email alerts
|

Flow through a convergence. Part 1: Critical conditions for unstable flow

Abstract: The critical conditions leading to fracture in elongation and different types of flow instabilities were examined in uniaxial elongation and in a capillary rheometer equipped with dies having different entry profiles. Either ductile or brittle fracture may be observed, ductile being related to necking of material. The critical stress approach was used to predict fracture in elongation. All linear polymers studied in this work exhibited ductile fracture in elongation, but the transition to brittle fracture is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 78 publications
3
20
0
Order By: Relevance
“…To determine the plateau modulus of HDPE, we used the coefficients of the relaxation time spectra derived from rheological characterizations of the literature. We found G 0 N = 649, 000 Pa at 190 • C with the data of Arda and Mackley [50] and G 0 N = 677, 000 Pa at 200 • C with those of Miller et al [51].…”
Section: Polyethylenessupporting
confidence: 75%
“…To determine the plateau modulus of HDPE, we used the coefficients of the relaxation time spectra derived from rheological characterizations of the literature. We found G 0 N = 649, 000 Pa at 190 • C with the data of Arda and Mackley [50] and G 0 N = 677, 000 Pa at 200 • C with those of Miller et al [51].…”
Section: Polyethylenessupporting
confidence: 75%
“…M a n u s c r i p t Kotera and Yamaguchi,5 Since the average molecular weight between entanglement couplings M e is inversely proportional to G N 0 , a polymer having high M e tends to show shark-skin failure at low shear stress [9]. Furthermore, it has been clarified that the narrow distribution of molecular weight also leads to the flow instability at low shear stress, which was theoretically derived using the concept of Deborah number [9].…”
Section: Introductionmentioning
confidence: 97%
“…Meller et al summarized that the shark-skin failure occurs beyond the critical shear stress at the die exit and the wavy melt fracture takes place beyond the critical elongational stress at the die entry [5]. Therefore, the rheological properties, especially strain-hardening behavior in elongational viscosity, affect the type of flow instability.…”
Section: Introductionmentioning
confidence: 98%
“…Since it is generally accepted that a high viscous polymer melt slips on the wall, the slippage can be the origin of surface instability [35,43,44]. Gross melt fracture is attributed to the flow instability at a die entrance, and associated with long time relaxation mechanism [38,[45][46][47][48][49][50][51]. Yamaguchi et al found that gross melt fracture of LDPE can be avoided by applying intense shear history, which weakens the relaxation mechanism associated with long-chain branches, by shear modification [51].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the longest relaxation time of the blend with a linear polyethylene having high molecular weight becomes longer than that of the LDPE [31]. The mechanisms of the flow instability at capillary extrusion have been investigated for a long time [25,26,[30][31][32][33][34][35][36][37][38]. It has been recognized that the flow instability can be classified into two types; one is rough surface, which is called as shark-skin failure, and the other is volumetric gross melt fracture.…”
Section: Introductionmentioning
confidence: 99%